2011
DOI: 10.1093/cid/cir334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of DNA Vaccines: Current Progress

Abstract: It was discovered almost 20 years ago that plasmid DNA, when injected into the skin or muscle of mice, could induce immune responses to encoded antigens. Since that time, there has since been much progress in understanding the basic biology behind this deceptively simple vaccine platform and much technological advancement to enhance immune potency. Among these advancements are improved formulations and improved physical methods of delivery, which increase the uptake of vaccine plasmids by cells; optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
242
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(248 citation statements)
references
References 46 publications
0
242
0
6
Order By: Relevance
“…In addition, cell-based production necessitates extensive purification steps, hampering efforts to respond to outbreaks rapidly. DNA-based vectors used for genebased vaccination (18)(19)(20) have shown efficacy in humans (21), but raise safety concerns due to the risk of mutagenic integration into the patient's genome (22,23). Nonretroviral RNA vaccines are attractive due to their inherent transience and absence of recombination or integration into the patient's genome.…”
mentioning
confidence: 99%
“…In addition, cell-based production necessitates extensive purification steps, hampering efforts to respond to outbreaks rapidly. DNA-based vectors used for genebased vaccination (18)(19)(20) have shown efficacy in humans (21), but raise safety concerns due to the risk of mutagenic integration into the patient's genome (22,23). Nonretroviral RNA vaccines are attractive due to their inherent transience and absence of recombination or integration into the patient's genome.…”
mentioning
confidence: 99%
“…Weak immune response elicited by DNA vaccines in clinical trials downscored their significance in humans. 59 However, Wang et al, reported that DNA vaccination was safe and elicited protective CD8C T cell responses in malaria-na€ ıve human subjects. 60 Poor immune response due to DNA vaccines can be overcome by codon optimization of the transgene encoded by the vector, the use of built-in adjuvants and the delivery approaches.59 DNA vaccines can be considered for immunization of infants, the principle target for HRSV vaccination, for 2 reasons: 1) they do not interfere with the preexisting maternal antibodies 61 ; 2) a single dose is sufficient to elicit long-term immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Another common approach is to incorporate into the vaccine plasmid, genes coding for cytokines, chemokines, co-stimulatory molecules and anti-apoptotic genes as "genetic adjuvants" [94][95][96][97]. Also, these genes can be delivered as separate plasmids.…”
Section: Adjuvantsmentioning
confidence: 99%